1996
DOI: 10.3354/dao026001
|View full text |Cite
|
Sign up to set email alerts
|

Genital and lingual warts in small cetaceans from coastal Peru

Abstract: ABSTRACT-We report on genital warts in dusky dolphins Lagenorhynchus obscurus, long-snouted common dolphins Delphinus capensis, bottlenose dolphins Tursiops truncatus and Burmeister's porpoises Phocoena spinipinnis caught in fisheries off central Peru. Lesions were observed inside the genital slit, on the skin adjacent to it, on the penis and on the vagina. Macro-and microscopical features of the lesions resemble those of benign genital warts associated with papillomavirus infection in humans Genital warts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
3
20
0
1
Order By: Relevance
“…Other inflammatory, infectious, or neoplastic diseases can at this stage not be ruled out. Though genital, cutaneous and oral papillomas (localized epithelium hyperplasia with a defined boundary and an intact basement membrane; Shah & Howley 1990) have been frequently described in odontocetes (Ge raci et al 1987, Lambertsen et al 1987, Bossart et al 1996, Van Bressem et al 1996, 1999, 2007b, Reh tanz et al 2006, Gottschling et al 2011, to the best of our knowledge, there are no published papers on cutaneous fibropapillomas in these marine mammals. Often caused by viruses in the family Papillomaviridae, fibropapillomas are commonly diagnosed on the skin of many terrestrial mammals including deer, camels, horses and zebras 1 where they can be plentiful and reach large sizes (Shope et al 1958, Sundberg & Nielsen 1981, Schulman et al 2003, Nel et al 2006.…”
Section: Malaysiamentioning
confidence: 97%
“…Other inflammatory, infectious, or neoplastic diseases can at this stage not be ruled out. Though genital, cutaneous and oral papillomas (localized epithelium hyperplasia with a defined boundary and an intact basement membrane; Shah & Howley 1990) have been frequently described in odontocetes (Ge raci et al 1987, Lambertsen et al 1987, Bossart et al 1996, Van Bressem et al 1996, 1999, 2007b, Reh tanz et al 2006, Gottschling et al 2011, to the best of our knowledge, there are no published papers on cutaneous fibropapillomas in these marine mammals. Often caused by viruses in the family Papillomaviridae, fibropapillomas are commonly diagnosed on the skin of many terrestrial mammals including deer, camels, horses and zebras 1 where they can be plentiful and reach large sizes (Shope et al 1958, Sundberg & Nielsen 1981, Schulman et al 2003, Nel et al 2006.…”
Section: Malaysiamentioning
confidence: 97%
“…Except for the harbor porpoise (Phocoena phocoena), molecular diagnosis was performed on all those cases, and the corresponding sequences are available in GenBank. Genital lesions of similar gross appearance have been associated with papillomaviruses in several cetacean species (Van Bressem et al 1996, 2007Gottschling et al 2011;Rehtanz et al 2012), so additional immunohistochemical and molecular studies are needed to identify the causative agent.…”
Section: Introductionmentioning
confidence: 99%
“…These cases were part of a sexually transmitted epidemic that involved adult male and female dolphins at both sites . Papillomavirusassociated orogenital papillomas have been described in other marine mammal species (Van Bressem et al 1996, 2007a, Bossart et al 2002, Ghim et al 2014). In our earlier study from 2003 to 2005, orogenital papillomas were described for the first time in association with virions ultrastructurally suggestive of a herpesvirus (Bossart et al 2005), and later with infection associated with the first reported American dolphin papillomavirus (Rehtanz et al 2006(Rehtanz et al , 2010.…”
Section: Discussionmentioning
confidence: 99%